Some deformations and extensions of the Ginzburg-Landau theory - Tellez, Cristhian Andrés Aguirre (2021)
In this work we study some deformations and extensions of the GinzburgLandau theory for the superconductor state. We will explain the history, advances, applications, future prospects and the numerical methods used to solve the time dependent Ginzburg-Landau Equations (TDGL). We will also study some extensions such as the superconductors with external currents and the multi-gap superconductor states, which have recently been considered in the literature. Special attention will be devoted to the effect of and inhomogeneous Ginzburg Landau parameter and some structural defects of the sample. Our results will be relevant in the phenomenological understanding of superconductivity and some technological applications of superconductor devices in lower and higher dimensions.